Governing European Communications: From Unification to Coordination - Michalis, Maria (Lexington Books, 2007)
The liberalization of communications markets, especially from the 1980s onward, has witnessed increased regulatory activity within but also above the national state. By examining the European case_concentrating on the European Union, the most advanced example of regionalism_Governing European Communications enhances understanding of the trend toward above-the-national-state regulation, its, drivers and its limitations. Analyzing in detail the origins, dynamics, and evolution of European-level communications governance in the postwar era, Michalis offers a single, comprehensive, and up-to-date account of telecommunications and television policies and regulation and their technological convergence.